2020
DOI: 10.1002/alr.22550
|View full text |Cite
|
Sign up to set email alerts
|

Understood? Evaluating the readability and understandability of intranasal corticosteroid delivery instructions

Abstract: Background Allergic rhinitis is a widespread disease that has significant quality‐of‐life ramifications. Symptoms include rhinorrhea, nasal obstruction, cough, and postnasal drip. Intranasal corticosteroids are a hallmark of treatment of allergic rhinitis. However, the benefits of treatment are dependent on correct nasal spray technique, of which many patients are not aware. Patient instructions are included with the purchase of these medications. The readability and understandability for these educational mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
4
8
0
Order By: Relevance
“…The understandability score of 73.65% 6 7.05% in this study is comparable but a bit higher than that of similar studies on other topics, which reported scores ranging from 62.8% to 66.0%. [44][45][46] The actionability score in the current study of 13.63% 6 22.47% is comparable to scores in the literature. 37,44,45 Although a high PEMAT-P score is better than a low score, there are no established guidelines for a PEMAT-P target to help guide writing.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The understandability score of 73.65% 6 7.05% in this study is comparable but a bit higher than that of similar studies on other topics, which reported scores ranging from 62.8% to 66.0%. [44][45][46] The actionability score in the current study of 13.63% 6 22.47% is comparable to scores in the literature. 37,44,45 Although a high PEMAT-P score is better than a low score, there are no established guidelines for a PEMAT-P target to help guide writing.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, PEMAT‐P understandability and actionability scores were low. The understandability score of 73.65% ± 7.05% in this study is comparable but a bit higher than that of similar studies on other topics, which reported scores ranging from 62.8% to 66.0% 44–46 . The actionability score in the current study of 13.63% ± 22.47% is comparable to scores in the literature 37,44,45 .…”
Section: Discussionsupporting
confidence: 49%
“…The American Medical Association (AMA) and the National Institutes of Health (NIH) recommend that patient education resources be written at a sixth-grade level to maximize patient comprehension. 1 Consequently, several publications in diverse medical specialties ranging from rheumatology, 2 plastic surgery, 3 and otolaryngology 4-6 have evaluated the readability and quality of online education website materials.…”
mentioning
confidence: 99%
“…However, there is no standard guideline for INCS use in Thailand. Consequently, the researcher gathered and adapted 12 techniques and steps used for INCS administration in previous studies [ 5 16 17 18 ], as well as a Dutch protocol [ 19 ], and from leafletless usage. Further, there are some differences in using the methods, as shown in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, there are some differences in using the methods, as shown in Table 4 . The 5 recommended essential steps were determined in reference to previous studies [ 14 16 17 18 19 ].…”
Section: Discussionmentioning
confidence: 99%